Experimental and quantum chemical study оn the DNA/protein binding and the biological activity of a rhodium(iii) complex with 1, 2, 4-triazole as an inert ligand. Issue 26 (22nd June 2020) - Petrović, Angelina; Živanović, Marko; Puchta, Ralph; Ćoćić, Dušan; Scheurer, Andreas; Milivojevic, Nevena; Bogojeski, Jovana
Abstract : A rhodium(iii ) complex with 1, 2, 4-triazole and a pincer type nitrogen-donor ligand was synthesized, and its interaction with biomolecules was examined. Abstract : The synthesis and structural characterization of a newly synthesized mononuclear rhodium(iii ) complex, Rhtrz, with a ligand (2, 2, 6-bis((4 S, 7 R )-7, 8, 8-trimethyl-4, 5, 6, 7-tetrahydro-1 H -4, 7-methanoindazol-3-yl)pyridine) and a ligand of 1, 2, 4-triazole, are presented in this paper. The kinetic interactions of the Rhtrz complex with essential biomolecules such as 5-GMP, L -Met, and GSH were examined. The study of the biological interactions was focused on the binding properties of the Rhtrz complex with CT-DNA and serum albumin. These interactions were investigated using UV-vis spectrophotometry, fluorescence spectroscopy, viscosity measurements, thermal denaturation studies, and electrophoresis. Fluorescence competition experiments with site-markers for BSA were used to locate the binding site of the Rhtrz -complex to the BSA. Molecular docking studies were carried out to obtain detailed binding information of the complex with CT-DNA, BSA, and HSA. Furthermore, the apparent distance between the donor (HSA) and acceptor (Rhtrz ) was determined using fluorescence resonance energy transfer (FRET). The thermodynamic properties and relative stabilities of the Rhtrz complex were examined, constructing the two model equation by DFT calculations (B3LYP(CPCM)/LANL2DZp). In vitro cytotoxicity and redox status on the human epithelial colorectal cancer cell line (HCT-116) and healthy human fibroblast cell line (MRC-5) were also investigated.